Isolated Co-Existence of Cerulean and Sutural Cataract - Cheau Wei Chin (Delhi Journal of Ophthalmology)
Cerulean and sutural cataracts are developmental cataracts that are relatively rare. In this photo essay we will discuss the nature of cerulean and sutural cataract. Usually no surgery will be needed until adulthood as their visual acuity is usually well-preserved.